Legal Analysis of Individual Companies in Supporting the Development of Micro and Small Enterprises in Indonesia - Ullia; Mohammad Roesli; Sri Anggraini Kusuma Dewi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This research aims to analyze the legal aspects of individual companies in supporting the development of micro and small enterprises (UMK) in Indonesia. Individual companies, which were introduced through Law Number 11 of 2020 concerning Job Creation and have been amended by Law Number 6 of 2023, offer convenience for MSEs in establishing legal entities. However, individual companies still face various legal obstacles that can hinder their effectiveness. This research identifies and evaluates these obstacles, including lack of clarity in regulations, conflicts of interest, and issues of owner responsibility and accountability. Through legal and conceptual approaches, this research examines the legal barriers of individual companies to the development of MSEs and provides recommendations for overcoming existing barriers. It is hoped that the findings from this research can contribute to the development of a legal framework that is more supportive for individual companies in order to advance MSEs in Indonesia.